What do you want from me - Pink Floyd; Guthrie, James; Gilmour, David; Sony Music Entertainment (UK). (United Kingdom : Sony Music Entertainment, 1995)
Contains the single taken from live album'P.U.L.S.E' which hit no. 1 on the Billboard 200 Album chart.
CD 1 : What Do You Want From Me / (4:10).
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Songs, English